Examining the Effects of Leadership, Organizational Commitment, and Well-Being on Teacher Performance - Meryza Coziffya; Robi Hendra; Arza Agustira; Muhammad Irzi Fadilah (Jurnal Paedagogy, 2026)
This study aims to examine the influence of leadership, commitment, and welfare on teacher performance in Muaro Jambi Regency. Teacher performance is regarded as a strategic factor in improving educational quality, in which principal leadership, organizational commitment, and teacher welfare are assumed to play significant roles. The study employed a survey research method using simple random sampling. Data were collected through Google Form–based questionnaires distributed to 213 junior high school teachers in Muaro Jambi Regency. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach with SmartPLS 4 software. The results indicate that all proposed hypotheses were supported. Transformational leadership has a positive and significant effect on organizational commitment (β = 0.417; p < 0.001), teacher welfare (β = 0.726; p < 0.001), and teacher performance (β = 0.365; p < 0.001). Teacher welfare also significantly influences organizational commitment (β = 0.447; p < 0.001) and teacher performance (β = 0.344; p < 0.001), while organizational commitment has a significant effect on teacher performance (β = 0.236; p < 0.001). The coefficient of determination (R²) for teacher performance is 0.738, indicating that leadership, welfare, and commitment collectively explain 73.8% of the variance in teacher performance. These findings confirm that effective principal leadership, adequate teacher welfare, and strong professional commitment are key determinants of teacher performance and overall educational quality.